Penetasan Telur Penyu Lekang (Lepidochelys olivacea Eschscholtz,1829) pada Lokasi Berbeda di Kawasan Konservasi Penyu Kota Pariaman - Nurhidayata Bin Syaiful; Jabang Nurdin; Indra Junaidi Zakaria (Jurnal Biologi Universitas Andalas, 2013)
Research about eggs hatching of olive ridley turtles (Lepidochelys olivacea Eschscholtz,1829) in the turtle conservation area of Pariaman City was conducted from October to January 2013. This research aims to determine a suitable location in eggs hatching of olive ridley turtles in the Turtle Conservation Area of Pariaman city. The research used experiment method with treatment A (beachsand near the shore) and B (beachsand near the sea), three repetitions in each location and 20 eggs per repeat. Results showed that the best location for hatching is beachsand near the shore with 80 % rate of hatching. The rate of hatching in beachsand near the sea is 37%. Environmental factors that influent rate of hatching are topography, temperature dan salinity.